ANALISIS KELAYAKAN DAN KEPRAKTISAN MEDIA INTERAKTIF BERASIS ANDROID (METERBAN) UNTUK MATERI IPAS KELAS V SEKOLAH DASAR - Wahdati, Dinda Saroh; Sulistiana, Devita; Marinda Sari Sofiyana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The goal of this study is to create an interactive media product for Android that delivers scientific content on the human digestive system. This research is categorized as research and development (R&D), sometimes referred to as development research, and focuses on developing learning tools. The research adopts the Sugiyono model, limited to level 7. Topics covered include potential and issues, data collection, product design, design validation, design revision, product testing, and product revision. The researcher developed an Android-based interactive media (Meterban), which received a material validation score of 80%, a media expert validation score of 94%, and a language expert validation score of 95.8%. Additionally, the teacher readability test results were classified as